USULAN STRATEGI PEMASARAN DI COFFE TONGLA MENGGUNAKAN METODE SWOT - Indra Gunawan; Muhammad Isnaini Hadiyyul Umam; Misra Hartati; Harpito; Rika Taslim (JURNAL PERANGKAT LUNAK, 2023)
Marketing strategy is a plan that allows a company to optimize the use of its resources to achieve marketing and company goals. Tongla Coffee is a place for young people to hang out. But there are still some areas in Pekanbaru that don't know about Tongla coffee, therefore Tongla coffee needs better promotion using social media (Instagram) and distributing browsers to all people both in Pekanbaru city and outside. Based on the sales graph from 2022, sales at Coffee Tongla experience fluctuations, namely sales experience ups and downs or are erratic every month. Customer data on consumers in January the sales target reached IDR 4,542,000, then decreased in February to reach IDR 3,375,000 and so on. This research must be able to answer the company's external and internal factors to achieve its goals, namely using the SWOT method. The SWOT method is needed as a first step in identifying and formulating several alternative company strategies based on the realities experienced by the company. The application of the Internal-External Matrix was carried out to carry out a detailed position analysis on Coffee Tongla, as well as to determine the right strategy. The results of this matrix are obtained from the IFE and EFE Matrix scores. Based on the results of score processing, the IFE Matrix obtained a score of 3.056 and the EFE Matrix obtained a score of 2.99. Using the IE Matrix, Tongla Coffee is in quadrant IV.